Influence of Nonpolio Enteroviruses and the Bacterial Gut Microbiota on Oral Poliovirus Vaccine Response: A Study from South India. (24th September 2018) - Praharaj, Ira; Parker, Edward P K; Giri, Sidhartha; Allen, David J; Silas, Sophia; Revathi, R; Kaliappan, Saravanakumar Puthupalayam; John, Jacob; Prasad, Jasmine Helan; Kampmann, Beate; Iturriza-Gómara, Miren; Grassly, Nicholas C; et al.
Abstract: Background: Oral poliovirus vaccine (OPV) is less immunogenic in low- or middle-income than in high-income countries. We tested whether bacterial and viral components of the intestinal microbiota are associated with this phenomenon. Methods: We assessed the prevalence of enteropathogens using TaqMan array cards 14 days before and at vaccination in 704 Indian infants (aged 6–11 months) receiving monovalent type 3 OPV (CTRI/2014/05/004588). Nonpolio enterovirus (NPEV) serotypes were identified by means of VP1 sequencing. In 120 infants, the prevaccination bacterial microbiota was characterized using 16S ribosomal RNA sequencing. Results: We detected 56 NPEV serotypes on the day of vaccination. Concurrent NPEVs were associated with a reduction in OPV seroconversion, consistent across species (odds ratio [95% confidence interval], 0.57 [.36–.90], 0.61 [.43–.86], and 0.69 [.41–1.16] for species A, B, and C, respectively). Recently acquired enterovirus infections, detected at vaccination but not 14 days earlier, had a greater interfering effect on monovalent type 3 OPV seroresponse than did persistent infections, with enterovirus detected at both time points (seroconversion in 44 of 127 infants [35%] vs 63 of 129 [49%]; P = .02). The abundance of specific bacterial taxa did not differ significantly according to OPV response, although the microbiota was more diverse in nonresponders at the time of vaccination. Conclusion: Enteric viruses have a greater impact on OPV response than the bacterial microbiota, with recent enterovirus infections having a greater inhibitory effect than persistent infections. Abstract : Nonpolio enteroviruses have a significant impact on oral poliovirus vaccine seroresponse irrespective of infecting serotype, whereas the bacterial gut microbiota does not affect OPV seroresponse significantly.